Functionalized Antifouling Polymer Brushes for Biospecific Surfaces - Erik J. Postma; Luc Scheres; Sissi deBeer; Andriy R. Kuzmyn; Han Zuilhof (Advanced Materials Interfaces, 2025)
Abstract Biosensors have become integrated into our lives. Current technology requires biosensors not only to have high sensitivity but also to have high specificity for one target, while repelling all other molecules and materials in the biological medium. These goals are met by surfaces that combine a biorecognition element and a high‐quality antifouling layer. In this review, we largely focus on polymer brushes that are grafted from the surface, as these are known to exhibit excellent antifouling properties. We also discuss how to functionalize these with biorecognition elements. Based on the current research on antifouling brushes, we recommend using poly(2‐hydroxypropylmethacrylamide) (HPMAA) and/or poly(carboxybetainemethacrylamide) (CBMAA) brushes, with a thickness between 20–30 nm. Furthermore, we note the importance of high polymer chain densities in such brushes and highlight that a proper comparison requires, among others, similar pre‐treatments. These antifouling brushes are biospecific after receptors are integrated with efficient coupling strategies. Here the opportunities and limitations of frequently used approaches of antifouling polymer brushes within biosensors are highlighted. Also, with the resulting combination of high specificity and low (bio‐)chemical noise levels, we envision an increase in the incorporation of novel polymer brushes for the development of stable biospecific sensors.